Sexually transmitted infections among men who have sex with men: a retrospective study in a tertiary care hospital - P., Prabahar; T., Ranganathan; C., Vijayabhaskar; Kalaivani, S.; L., Balamurugan; P., Sivasankri (International Journal of Research in Medical Sciences, 2017)
Background: Men who have sex with Men (MSM) have a higher prevalence of HIV and other sexually transmitted infections (STI) than the heterosexual men. In India, NACP recommendations to reduce HIV prevalence among MSM include early detection of HIV and other STI by screening and treatment. We conducted a study of STIs among MSM attending our OPD. The aim of the study was to assess the prevalence of STIs in MSM attending our OPD. Methods: 1215 MSM among 9008 patients who attended our OPD between June 2015 and May 2016 were included in the study. Detailed history was taken and clinical examination carried out. Urethral discharge and urine samples were tested for Gonococcal infection. Smears from ulcers were tested for Syphilis, Chancroid, Herpes and Donovanosis. Serum samples were tested for HIV and other STIs like Syphilis and Herpes. Results: Among 1215 MSMs, 55 (4.5%) tested positive for VDRL and TPHA and 33 (2.7%) tested positive for HIV. 24 (2%) had urethritis (10 GU and 14 NGU), 15 (1.25%) had Balanophosthitis, 12 (1%) had genital herpes, 9 (0.75%) had genital scabies, 6 (0.5%) had Genital Wart and 2 (0.16%) had Molluscum contagiosum. Prevalence of these STIs were far higher in MSMs than in heterosexual men. Conclusions: This study highlights the higher prevalence of STIs among MSMs and the need for early intervention and treatment in this high-risk population.